Penilaian Kriteria Green Building Pada Bangunan Hotel Harper Wahid Hasyim Medan - Ahmad Wahyu Guzri; Irwan Irwan; Amsuardiman Amsuardiman (Jurnal Ilmiah Teknik Sipil dan Arsitektur (JITAS), 2022)
The issue currently being faced by the global community is the issue of global warming, which researchers believe is caused by development activities. Currently, every series of development activities has the potential for negative impacts on the environment, so that construction actors need to have awareness and knowledge in minimizing these negative impacts. One solution that can be done by construction actors in building is to apply the concept of Green Building. The writing of this study aims to determine the results of measuring green building criteria based on the Greenship-GBCI standard in buildings by conducting questionnaires and verification interviews. Based on the data collected and the calculations that have been made at the Harper Hotel Building against the 41 Greenship criteria, the building obtained a total of 64 points out of a maximum of 117 points. Thus, the building is considered to have met the criteria as a built building that applies the Green Building concept according to the GBCI assessment tool and has a minimum standard value of rating fulfillment of 58 points for the Gold rating